Teachers’ perceptions and experiences of gender in physical education across diverse cultural contexts - Makrooni, Golaleh; Kalari, Joonas; Mohammed, Warhel Asim; Lagestad, Pål (Frontiers in Education, 2025)
IntroductionPhysical Education (PE) plays a vital role in promoting lifelong wellbeing, with gender equity being a key component of both individual and community health. Understanding how gender is perceived and addressed in PE settings is essential for developing inclusive and effective educational practices. While gender has been widely studied in education, little comparative research has examined how PE teachers understand and address it in relation to curricula, pedagogy, and socio-cultural norms. This study explores the perceptions and experiences of primary school PE teachers in Finland and the Kurdistan Region of Iraq (KRI), focusing on how cultural, social, curricular, and pedagogical factors shape the positioning of gender in PE.MethodsThe study employed a qualitative approach using semi-structured, in-depth interviews with 14 PE teachers—eight from Finland and six from KRI to examines PE teachers’ perceptions and experiences related to gender in PE. During the 60–90 min interviews, the PE teachers also looked at two typical PE lessons (both indoor and outdoor, each for a duration of 15 min) for fifth grade PE classes in the other region.ResultsThe thematic analysis revealed several categories: in the KRI, these included gender roles, socio-cultural norms and attitudes, flexible pedagogy in PE, awareness of gender differences and impacts, and gender and curriculum; in Finland, the themes were pedagogical flexibility and freedom, and awareness of gender differences and impacts. Overall, the findings of this study indicate that both Finnish and KRI teachers reported that gender differences were not prominent in primary school, particularly at younger ages. Nonetheless, all teachers were aware of the potential impacts of gender on PE.DiscussionThe findings of this study revealed both similarities and differences in teachers’ perceptions and experiences regarding PE teaching and activities, particularly when considering gender. Both Finnish teachers and those from the KRI demonstrated awareness of gender differences in physical abilities, emotions, and psychological traits. However, Finnish teachers primarily focused on fostering joy and encouraging movement tailored to each student’s interests and circumstances. In contrast, KRI teachers also exhibited flexibility in designing activities that catered to the physical and emotional needs of both boys and girls. The results of this study can inform the development of more inclusive educational programs for PE teachers, equipping them with culturally adopted pedagogical approaches to reduce gender inequality in PE through innovative and contextually relevant methods that consider cultural and social factors.